2008
DOI: 10.1007/s11095-008-9540-4
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable Submicron Protein Particles by Thin Film Freezing

Abstract: The cooling rates of 10(2) K/s, intermediate to those in lyophilization (1 K/min) and spray freeze-drying (SFD) (10(6) K/s), were sufficiently fast to produce sub-micron protein particles with surface areas of 31-73 m2/g, an order of magnitude higher than in lyophilization. In addition, the low surface area/volume ratio (32-45 cm(-1)) of the gas-liquid interface led to minimal protein adsorption and denaturation relative to SFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 69 publications
(127 reference statements)
4
106
0
Order By: Relevance
“…It was found that minimizing gas-liquid interface can improve protein stability by limiting the amount of protein that can absorb to the interface. The surface area to volume ratio of the gas-liquid interface in TFF was 2 orders of magnitude lower than in SFD, leading to much less protein adsorption and aggregation (Engstrom et al 2008 ) .…”
Section: Advantages Of Tff Processmentioning
confidence: 92%
See 2 more Smart Citations
“…It was found that minimizing gas-liquid interface can improve protein stability by limiting the amount of protein that can absorb to the interface. The surface area to volume ratio of the gas-liquid interface in TFF was 2 orders of magnitude lower than in SFD, leading to much less protein adsorption and aggregation (Engstrom et al 2008 ) .…”
Section: Advantages Of Tff Processmentioning
confidence: 92%
“…In TFF process, the size of the unfrozen channels was suffi ciently thin and the increase in the viscosity of the unfrozen solution was suffi ciently fast to be able to achieve similar particle sizes and morphologies as for the moderately faster process, SFL, and the much faster process, SFD (Engstrom et al 2008 ) .…”
Section: Advantages Of Tff Processmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Briefly, Itz (0.4%, w/v) was dissolved in 1,4 dioxane and dripped onto a stainless steel surface that was cooled by dry ice to maintain a surface temperature of 223 K at a flow rate of 4 mL/min through a 17 gauge (1.1 mm ID, 1.5 mm OD) stainless steel syringe needle. Upon impact with the steel surface, the droplets spread into thin disks and froze.…”
Section: Thin Film Freezing (Tff)mentioning
confidence: 99%
“…Relative to top-down approaches (milling and homogenization processes), precipitation technologies are typically more controlled, in terms of consistently producing particles with similar morphologies, and offer the ability to achieve higher drug loadings (Matteucci et al 2006Overhoff et al 2007a, b ;Engstrom et al 2007Engstrom et al , 2008Rasenack and Muller 2002 ;Rogers et al 2004 ;Shoyele and Cawthorne 2006 ;Vaughn et al 2005 ;Young et al 2000 ) . Precipitation processes are often easier to scale-up and require less particle handling than milling and homogenization operations, resulting in higher process yields and lower impurity risks, as well as simplifi ed cleaning and sterilization procedures (Rogers et al 2001a ) .…”
Section: Introductionmentioning
confidence: 99%